The Relationship Between Work Motivation and the Performance of Posyandu Cadres in the Kronjo Health Center Area in 2022 - Wijayanti, Novi; Vanchapo, Antonius Rino (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Work motivation and work performance have a very close relationship to performance. Cadres have a very high linkage and are always active in posyandu activities so that it will improve the performance of posyandu cadres. Motivation is defined as strength, encouraging a person or group of people to achieve certain achievements according to what is desired. This study aims to determine the relationship between work motivation and the performance of posyandu cadres in the Kronjo Health Center area in 2022. This research is a quantitative study using a cross-sectional research design. Based on the results of statistical tests using the Spearman rank correlation test, it was obtained a p-value = 0.043, this shows that the value of p = 0.043 is still smaller than ? 0.05, it is certain that between variable 1 and variable 2 there is a significant relationship between work motivation and cadre performance Posyandu in the Kronjo Sub-District Community Health Center in 2022 (0.043<0.05). The results of the Spearman rank statistical test obtained a p-value = 0.043, meaning that there is a significant relationship between work motivation and the performance of posyandu cadres in the Kronjo District Health Center area in 2022. Because it is still smaller than ? < 0.05, (0.043 <0.05). moderate motivation is likely to perform sufficiently or insufficiently. It is suggested that the Kronjo District Health Center can improve training and provide different rewards for active cadres so that the performance of Posyandu cadres in the Kronjo Health Center Work Area is even better.